Synthetic studies for photo-triggered release of bioconjugate porphyrin photosensitisers in photodynamic therapy - Bakar, Mohd Bakri (Trinity College (Dublin, Ireland). School of Chemistry, 2009)
The objective of this research was to synthesise porphyrin linked-bioconjugate photosensitisers that can be released upon irradiation with UV light; aiming to improve photodynamic cancer therapy efficiency. This photoreleased-bioconjugate system has potential for use in targeted photosensitiser delivery with a light-triggered control release mechanism. Several approaches were employed towards linking porphyrins to the bioconjugates using thio and o-nitrobenzyl labile linkers. The classic 1.3-dithiane-2-yl synthon residue is an useful anion which has been used both as a functional and protected formyl group. Based on Umpolung studies, SnAr reactions via RLi method were carried out to introduce dithianyl residue into porphyrin macrocycle and act as the formyl synthon. The reactivity of related dithio analogues was later investigated to explore their basic chemistry. Subsequent work was focused on constructing labile photocleavable systems using spirobisdithiane and trithiane residues. It has been shown that mono-lithio derivatives of the spirobisdithiane and trithiane can be utilised as nucleophiles for the direct substitution of different porphyrins. However, the possibility to direct cross linking of two to three porphyrins or linking porphyrin to a bioconjugate via di- and trilithiated anion species of spirobisdithiane and trithiane was not realised. In most cases, butylation occurred as the competitive reaction. Interestingly, the free base substituted porphyrins exhibit highly photosensitivity towards ambient light and easily converted to formyl porphyrins.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin